2011
DOI: 10.1186/2047-783x-16-12-531
|View full text |Cite
|
Sign up to set email alerts
|

A case of wound dual infection with Pasteurella dagmatis and Pasteurella Canis resulting from a dog bite - limitations of Vitek-2 system in exact identification of Pasteurella species

Abstract: BackgroundPasteurella species, widely known as indigenous orgganisms in the oral and gastrointestinal floras of many wild and domestic animals, are important pathogens in both animals and humans. Human infections due to Pasteurella species are in most cases associated with infected injuries following animal bites. We encountered a rare case of dual infections caused by different two Pasteurella species occurred in a previously healthy 25-year-old female sustaining injury by a dog-bite.MethodologyExudates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Pasteurella spp. infrequently cause systemic infectious diseases and mostly infect patients with underlying diseases [ 20 ]. Capnocytophaga cynodegmi canine oral taxon 254 clone ZX121, the causative agent of bite wound infections [ 21 ], was also identified (485 reads).…”
Section: Resultsmentioning
confidence: 99%
“…Pasteurella spp. infrequently cause systemic infectious diseases and mostly infect patients with underlying diseases [ 20 ]. Capnocytophaga cynodegmi canine oral taxon 254 clone ZX121, the causative agent of bite wound infections [ 21 ], was also identified (485 reads).…”
Section: Resultsmentioning
confidence: 99%
“…In the second two studies of Griffin and Holt8 and Meyers and others11, the isolates were identified with help of Analytic Profile Index tests (API) by BioMerieux. P dagmatis is not registered in the identification table of API 20 NE, and thus this method is not able to identify the bacterium 3. As this is a standard identification method, this could lead to a misidentification of P dagmatis and subsequently an underestimation of its frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria from the Pasteurellaceae family cause zoonotic infections in humans, with P multocida and P canis being the most common Pasturella species reported in human infections ( 7 , 8 ). Infections caused by Pasteurella species are typically introduced by animals, particularly cat or dog bites, but also occasionally by other animals, and often manifest as skin or soft tissue infections ( 7 9 ). Sometimes, animal contact is not prominent in the initial patient history ( 10 , 11 ) ( Table 3 ).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Interestingly, while Pasturella species infrequently cause systemic infectious disease, in our review of the literature, when P dagmatis infections are reported, they appear to be frequently associated with severe disseminated infection including bacteremia. Coinfections of P dagmatis with another Pasturella species have also been observed ( 9 , 12 , 22 ); therefore, it is important for the laboratory to test multiple morphotypes from the plate to ensure that >1 Pasturella species is not present.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%